Manipulating the bioactivity of hydroxyapatite nano-rods structured networks: Effects on mineral coating morphology and growth kinetic - D'elía, Noelia Laura (2013)
Background: Nano-hydroxyapatite particles have better bioactivity than the coarse crystals. So, they can be utilized for engineered tissue implants with improved efficiency over other materials. The development of materials with specific bioactive characteristics is still under investigation. Methods: The surface properties of four hydroxyapatitematerials templated by differentmicelle-polymer structured network are studied. The synergistic interaction of each block copolymer in contact with CTAB rod-like micelles results in crystalline HAp nano-rods of 25-50 nm length organized in hierarchical structures with different micro-rough characteristics. Results: It was observed that the material in vitro bioactivity strongly depends on the surface structure while in a minor extent on their Ca/P ratio. So, MIII and MIV materials with Skewness parameter Rsk N 2.62 favored the formation on their surfaces of net-like phase with a high growth kinetic constant; while MI and MII (Rsk = 2.62) induced the appearance of spherulitic-like structures and a growth rate 1.75 times inferior. Material biocompatibility was confirmed by interaction with rat calvarial osteoblasts. Conclusions: The different structures growth is attributed to a dissimilar matching of crystal planes in the material and the apatite layer formed. In specific synthesis conditions, a biocompatible material with a Ca/P ratio close to that for the trabecular bone and a morphology that are considered essential for bone-bonding was obtained. General significance: The creation of implantable devices with a specific bioactive characteristic may be useful to manipulate the attachment of cells on mineral coating directly affecting the stability and life of the implant. This article is part of a Special Issue entitled: Protein trafficking & Secretion.